Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 199733 by Rupesh123 last updated on 08/Nov/23

Answered by mr W last updated on 08/Nov/23

x^6 −x^4 +1=0  (x^2 )^3 −(x^2 )^2 +1=0  x_1 ^2 +x_2 ^2 +x_3 ^2 =1  x_1 ^2 x_2 ^2 +x_2 ^2 x_3 ^2 +x_3 ^2 x_1 ^2 =0  x_1 ^2 x_2 ^2 x_3 ^2 =−1  (x_1 ^2 +x_2 ^2 +x_3 ^2 )^2 =1^2   x_1 ^4 +x_2 ^4 +x_3 ^4 +2(x_1 ^2 x_2 ^2 +x_2 ^2 x_3 ^2 +x_3 ^2 x_1 ^2 )=1  x_1 ^4 +x_2 ^4 +x_3 ^4 +2×0=1  ⇒x_1 ^4 +x_2 ^4 +x_3 ^4 =1    α_k ^(12) =(α_k ^6 )^2 =(α_k ^4 −1)^2 =α_k ^8 −2α_k ^4 +1     =α_k ^2 (α_k ^4 −1)−2α_k ^4 +1     =α_k ^6 −α_k ^2 −2α_k ^4 +1     =α_k ^4 −1−α_k ^2 −2α_k ^4 +1     =−(α_k ^2 +α_k ^4 )  Σ_(k=1) ^6 α_k ^(12)  =−2Σ_(k=1) ^3 (α_k ^2 +α_k ^4 )        =−2(1+1)=−4 ✓

$${x}^{\mathrm{6}} −{x}^{\mathrm{4}} +\mathrm{1}=\mathrm{0} \\ $$$$\left({x}^{\mathrm{2}} \right)^{\mathrm{3}} −\left({x}^{\mathrm{2}} \right)^{\mathrm{2}} +\mathrm{1}=\mathrm{0} \\ $$$${x}_{\mathrm{1}} ^{\mathrm{2}} +{x}_{\mathrm{2}} ^{\mathrm{2}} +{x}_{\mathrm{3}} ^{\mathrm{2}} =\mathrm{1} \\ $$$${x}_{\mathrm{1}} ^{\mathrm{2}} {x}_{\mathrm{2}} ^{\mathrm{2}} +{x}_{\mathrm{2}} ^{\mathrm{2}} {x}_{\mathrm{3}} ^{\mathrm{2}} +{x}_{\mathrm{3}} ^{\mathrm{2}} {x}_{\mathrm{1}} ^{\mathrm{2}} =\mathrm{0} \\ $$$${x}_{\mathrm{1}} ^{\mathrm{2}} {x}_{\mathrm{2}} ^{\mathrm{2}} {x}_{\mathrm{3}} ^{\mathrm{2}} =−\mathrm{1} \\ $$$$\left({x}_{\mathrm{1}} ^{\mathrm{2}} +{x}_{\mathrm{2}} ^{\mathrm{2}} +{x}_{\mathrm{3}} ^{\mathrm{2}} \right)^{\mathrm{2}} =\mathrm{1}^{\mathrm{2}} \\ $$$${x}_{\mathrm{1}} ^{\mathrm{4}} +{x}_{\mathrm{2}} ^{\mathrm{4}} +{x}_{\mathrm{3}} ^{\mathrm{4}} +\mathrm{2}\left({x}_{\mathrm{1}} ^{\mathrm{2}} {x}_{\mathrm{2}} ^{\mathrm{2}} +{x}_{\mathrm{2}} ^{\mathrm{2}} {x}_{\mathrm{3}} ^{\mathrm{2}} +{x}_{\mathrm{3}} ^{\mathrm{2}} {x}_{\mathrm{1}} ^{\mathrm{2}} \right)=\mathrm{1} \\ $$$${x}_{\mathrm{1}} ^{\mathrm{4}} +{x}_{\mathrm{2}} ^{\mathrm{4}} +{x}_{\mathrm{3}} ^{\mathrm{4}} +\mathrm{2}×\mathrm{0}=\mathrm{1} \\ $$$$\Rightarrow{x}_{\mathrm{1}} ^{\mathrm{4}} +{x}_{\mathrm{2}} ^{\mathrm{4}} +{x}_{\mathrm{3}} ^{\mathrm{4}} =\mathrm{1} \\ $$$$ \\ $$$$\alpha_{{k}} ^{\mathrm{12}} =\left(\alpha_{{k}} ^{\mathrm{6}} \right)^{\mathrm{2}} =\left(\alpha_{{k}} ^{\mathrm{4}} −\mathrm{1}\right)^{\mathrm{2}} =\alpha_{{k}} ^{\mathrm{8}} −\mathrm{2}\alpha_{{k}} ^{\mathrm{4}} +\mathrm{1} \\ $$$$\:\:\:=\alpha_{{k}} ^{\mathrm{2}} \left(\alpha_{{k}} ^{\mathrm{4}} −\mathrm{1}\right)−\mathrm{2}\alpha_{{k}} ^{\mathrm{4}} +\mathrm{1} \\ $$$$\:\:\:=\alpha_{{k}} ^{\mathrm{6}} −\alpha_{{k}} ^{\mathrm{2}} −\mathrm{2}\alpha_{{k}} ^{\mathrm{4}} +\mathrm{1} \\ $$$$\:\:\:=\alpha_{{k}} ^{\mathrm{4}} −\mathrm{1}−\alpha_{{k}} ^{\mathrm{2}} −\mathrm{2}\alpha_{{k}} ^{\mathrm{4}} +\mathrm{1} \\ $$$$\:\:\:=−\left(\alpha_{{k}} ^{\mathrm{2}} +\alpha_{{k}} ^{\mathrm{4}} \right) \\ $$$$\underset{{k}=\mathrm{1}} {\overset{\mathrm{6}} {\sum}}\alpha_{{k}} ^{\mathrm{12}} \:=−\mathrm{2}\underset{{k}=\mathrm{1}} {\overset{\mathrm{3}} {\sum}}\left(\alpha_{{k}} ^{\mathrm{2}} +\alpha_{{k}} ^{\mathrm{4}} \right) \\ $$$$\:\:\:\:\:\:=−\mathrm{2}\left(\mathrm{1}+\mathrm{1}\right)=−\mathrm{4}\:\checkmark \\ $$

Commented by Rupesh123 last updated on 08/Nov/23

Perfect, sir!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com